ANALISIS PIDATO PRESIDEN PRABOWO: JALAN PANJANG PEMBERANTASAN KORUPSI DI INDONESIA - , Tabah Maryanah (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2025)
The president's speech during the inauguration is a very important moment because the content of the speech is a reflection of the president's vision and mission and will be a reference for the formation of public opinion. This article is an analysis of President Prabowo's speech related to corruption eradication in Indonesia. The research method is qualitative with the main data source of President Prabowo's speech during the inauguration and related news and articles. The data was analyzed using discourse analysis to identify the main themes related to corruption eradication and its challenges. In his speech, President Prabowo has a promising mission to prevent and prosecute corruption. President Prabowo is committed to realizing a clean and trustworthy government. His strategy is to implement system improvements, strict law enforcement, digitalization of political and government processes and require all elements of leadership to set an example in the fight against corruption. However, corruption in Indonesia has been so severe that it has hampered social, political and economic development. This article will explore that despite the President's commitment, corruption eradication has opportunities but also has high challenges.